Pengaruh Kualitas Layanan Aplikasi DANA Terhadap Kepuasan Pengguna dalam Melakukan Transaksi Secara Online Sebagai Alat Pembayaran Elektronik (E-Payment) Di Daerah Istimewa Yogyakarta - Ratnaningtyas, Endah Marendah; Hulub, Delisman Jaya; Puspitaningnalac, Diva Rifdah Rizkia; Jumadi (Journal of Economics and Management, 2024)
As technology and the internet develop, more and more people are using itE-payment as an easy and fast solution in conducting transactions online. This study aims to determine and analyze the effect of service quality on user satisfaction E-payment DANA. The DANA application is an application that supports non-cash payments or Mobile Payment. The type of research used is quantitative, for data collection by distributing questionnaires. The number of samples in this study were 100 respondents. The sample taken is the people of the Special Region of Yogyakarta who use DANA. The data analysis method used in this study is multiple linear regression, t test, F test and test of the coefficient of determination. Based on the test results that have been carried out, the results of this study indicate that partially, reliability, assurance, and responsiveness have a significant effect on user satisfaction. and simultan eously reliability, assurance, and responsiveness have a significant effect on user satisfaction. Keywords: Quality Reliability, Guarantee, Responsiveness, User Satisfaction, DANA